(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This paper describes the use of Real Time graphic applications as educational tools, specifically oriented to working with people who have certain learning difficulties. We first focus on identifying the most relevant traits (from a psychological point of view) of those disorders, then we continue by analysing the advantages of graphics in Real Time in this context, and how they can be used to complement the conventional teaching methods.